Construcción y puesta en marcha de un reactor tipo Batch a escala piloto para el tratamiento terciario de aguas residuales municipales de la ciudad de Barranquilla (2019)
The wastewater treatment systems contribute to the high concentrations of nutrients that do not affect the quality of the water bodies receivers, nor limit the economic activities that derive from them. Therefore, in the present research work a Batch reactor was built for the tertiary treatment of municipal wastewater, which had two fixed-bed bioreactors, a supply tank and two pumps for water circulation and air supply. For the startup of the system, two scenarios were taken into account, the simple treatment system (with circulation and aeration) and the system with multiple filtration including microalgae and bioadsorbent material, in both cases the parameters of the biological oxygen demand (DBO), chemical oxygen demand (DQO), phosphates, nitrates, nitrites and control parameters (alkalinity, pH, dissolved oxygen, among others) were evaluated; aliquots were taken every 2 and 4 hours in the two assemblies. Subsequently, through the analysis of variance, the system was evaluated based on the percentages of removal; in the simple treatment system (STS), greater removal was observed in the DQO parameter with 83,7% and lower in the alkalinity with 1,04%. However, the multiple filtration system (SFM) offered greater removal, mainly in the nutrients, obtaining a percentage of 100% for the nitrites and showing a lower efficiency in the reduction of alkalinity due to the characteristics of the bioadsorbent material, with the presence of CaCO3.